(3Yde GdEOGQI GdYGeI h GdEOGQI GdeGdjIs - (3QaYJ CMeO(B, (3GdSHYs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2008)
(3jVe eaGgje GdEOGQI, GdEOGQI GdYGeI ef GdhLgI GdabgjI, GdeQcRjI hGddGeQcRjI, GdEOGQI GdeGdjI eaghegG hYfGUQgG, EYOGO GdJfXje GdEOGQj ddefTCI, hXGFa GdeTQhY, GdJNWjW, GdQbGHI hGdJMajR, GdEOGQI hGdeSJbHds
(3HjHdjhZQGajG(B: (3U U(B.207-208s
Keywords: (3GdEOGQI GdYGeIs; (3GdEOGQI GdeGdjIs